Matched tissue-blood whole-exome sequencing improves detection of genetic etiologies in pediatric drug-resistant epilepsy - Ruan, Yuanyuan; Chen, Li; Xia, Shengying; Lu, Qing; Wang, Jing; Zhu, Feng; Li, Nannan; Du, Hao; Sun, Dan (Frontiers in Pediatrics, 2026)
BackgroundImproving the diagnostic rate of genetic etiologies in pediatric drug-resistant epilepsy (DRE) is of critical importance, as it provides valuable guidance for clinical management in this challenging patient population.MethodsIn this study, matched tissue–blood whole-exome sequencing (WES) was performed on lesional brain tissue and peripheral blood from 21 patients diagnosed with DRE who had undergone resective epilepsy surgery, in order to assess its diagnostic yield.ResultsThe final cohort therefore consisted of 21 pediatric patients with DRE. The patients’ ages ranged from 0.2 to 10.7 years, with a mean age of 5.2 years. Eleven were male and ten were female. Matched tissue-blood WES successfully identified the genetic etiology in six pediatric patients with drug-resistant epilepsy, yielding a diagnostic rate of 28.6% (6/21). This rate was higher than that achieved using blood-only WES (19.0%, 4/21) or clinical and imaging evaluations alone (9.5%, 2/21). Among these six positive cases: Patients 2 and 7 carried deletion and splice-site variants in the DEPDC5 gene, respectively, and these findings were detected in both blood and diseased brain tissue; Patients 14 and 20 both had missense variants in the TSC2 gene, detected in both blood and diseased brain tissue; Patients 8 and 16 had negative blood WES results, but somatic mosaic BRAF variants were detected in the diseased brain tissue, with mosaic levels of 20.2% and 13.5%, respectively.ConclusionsMatched tissue–blood WES facilitates the diagnostic yield in pediatric drug-resistant epilepsy, highlighting its critical value in detecting genetic variants that may be missed by blood-only testing and providing essential support for precision diagnosis and therapy.